Outside In - Underwood, Deborah; Derby, Cindy (Boston, 2020)
Illustrations and easy-to-read text reveal ways nature affects our everyday lives, such as providing food and clothing, and showing when to go to bed and when to get up.
Keywords: Mindfulness (Psychology) -- Juvenile fiction; Nature fiction